1996
DOI: 10.1007/bf02505208
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of systolic pressures of pulmonary artery and right ventricle using contrast-enhanced doppler echocardiography: Comparative study using sonicated albumin or glucose solution

Abstract: Evaluation of pulmonary arterial pressure is essential for the diagnosis and management of patients with congenital heart disease; it is usually done by cardiac catheterization. An alternative, noninvasive method may be clinically more useful. The purpose of this study was to assess the usefulness of the noninvasive determination of systolic pressure of the pulmonary artery and right ventricle by contrast-enhanced Doppler echocardiography. We selected 30 pediatric patients (28 with trivial or nonsignificant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…One of the limitations of this technique is that the backscatter generated by this technique is a relatively course, heterogeneous and unstable reflector of ultrasound. Limitations of agitated saline, most likely due to the relatively large size, low number, short term and unstable nature of the bubble [24] , [25] include over-estimation of the velocity in patients with trivial tricuspid regurgitation and not having as good correlation with catheter derived RVSP compared to an air-blood-saline contrast mixture [22] , [26] , [27] , [28] . As such, it is not uncommon for agitated saline to produce course, incomplete spectral Doppler envelopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the limitations of this technique is that the backscatter generated by this technique is a relatively course, heterogeneous and unstable reflector of ultrasound. Limitations of agitated saline, most likely due to the relatively large size, low number, short term and unstable nature of the bubble [24] , [25] include over-estimation of the velocity in patients with trivial tricuspid regurgitation and not having as good correlation with catheter derived RVSP compared to an air-blood-saline contrast mixture [22] , [26] , [27] , [28] . As such, it is not uncommon for agitated saline to produce course, incomplete spectral Doppler envelopes.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic contrast microspheres have been used in routine clinical practice since the mid 1990's [7] , [30] , [31] . As a strong backscatterer of ultrasound, these agents can also be used to optimise a spectral Doppler signal, either on the left or right side of the heart [28] , [29] , [32] , [33] , [34] , [35] . However, all these studies have used a first generation contrast agent such as sonicated albumin or Levovist © (Bayer, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is now a lot of experimental evidence: (1) to support the accuracy of this technique as an index of peak pulmonary systolic pressure in both euoxia (Yock et al 1986) and hypoxia (Allemann et al 2000); and (2) to show that peak systolic pressure is tightly related to the mean pulmonary arterial pressure (Yock et al 1986;Chan et al 1987;Ishii et al 1996).…”
Section: Liu and Othersmentioning
confidence: 99%
“…Characterization of tricuspid valve regurgitation flow with Doppler can be valuable in the noninvasive estimation of RV and PA systolic pressure when the peak regurgitation velocity is combined with estimates of RA pressure. 43 Furthermore, determining the severity of tricuspid regurgitation can help ascertain clinical utility of thermodilution ejection fraction measurements. Pulmonary arterial images in cross-section and Doppler flow characteristics can be used to assess RV afterload from PA distensibility, contractility from flow acceleration, and cardiac output from the product of PA area and velocity.38,44 Some investigators have reported that Doppler characterization of hepatic venous flow patterns also provides valuable indirect information regarding right heart function.…”
Section: Right-heart Catheterizationmentioning
confidence: 99%